Business rules modeling using OCL - Sosunovas, Sergejus; Vasilecas, Olegas (Lietuvos matematikos rinkinys, 2004)
Business rules are important components of every business system. Therefore creating information systems aimed to support business it is important to specify business rules unambiguously. Formal specification languages have different power specifying business rules of different types. This work argues that formal language OCL powerful enough to specify business rules of main types.